The Effectiveness of The Numbered Heads Together Model Assisted By Audiovisual Media in Teaching News Text Speaking Based on Students’ Learning Styles - Nanda Fatimatuz Zahro; Rahayu Pristiwati (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
This study aims to examine the effectiveness of the Numbered Heads Together (NHT) learning model assisted by audiovisual media and to analyze the role of learning styles (visual, auditory, and kinesthetic) in students’ news text speaking skills at Madrasah Aliyah. The research employed a quantitative approach using a quasi-experimental design. The subjects of this study were 23 eleventh-grade students of class XI IPA 2 at MA NU Nurussalam Kudus. Data were collected through speaking performance tests and learning style questionnaires, which were subsequently analyzed using a paired t-test and one-way analysis of variance (ANOVA). The findings reveal that the implementation of the Numbered Heads Together model significantly improved students’ news text speaking skills, as indicated by an increase in the mean score from 58.04 in the pre-test to 79.69 in the post-test. The results of the paired t-test further confirm this improvement (t = −13.84, Sig. = 0.000). In addition, the ANOVA results show a significant difference in speaking achievement based on students’ learning styles (Sig. = 0.004; p < 0.05), suggesting that the effectiveness of the learning model is influenced by learners’ learning style profiles. Therefore, it can be concluded that the Numbered Heads Together model assisted by audiovisual media is effective in enhancing students’ news text speaking skills, and that speaking instruction should take learning styles into consideration.